Myeloid ACAT1/SOAT1: a novel regulator of dyslipidemia and retinal neovascularization - Syed A. H. Zaidi; Ruth B. Caldwell; Modesto A. Rojas (npj Metabolic Health and Disease)
Abstract Pathological retinal neovascularization (RNV) is a major cause of vision loss and blindness during ischemic retinopathies. Our investigations in the mouse model of oxygen-induced retinopathy (OIR) demonstrate a novel mechanism of pathological RNV and neurovascular injury. We show that OIR-induced activation of macrophage/microglial cells, retinal inflammation, and pathological RNV are mediated by increases in cholesterol ester (CE) formation due to activation of the acyl-CoA: Cholesterol Acyltransferase 1/Sterol O-Acyltransferase 1 (ACAT1/SOAT1) enzyme.